ANALYSIS OF THE IMPLEMENTATION OF PPH 21 USING THE NET METHOD AS AN EFFICIENCY EFFORT OF CORPORATE INCOME TAX BURDEN AT PT AQILA DUTA BALISFA - Yaumi, Sri; Nikmah, Zahrotun; Berlyn Hakim, Mesra; Nataliawati, Rita (JURNAL EKBIS, 2024)
The government is trying to maximize budget revenue to increase National Development sustainably..Tax is the largest source of income for the country. However, from an economic perspective, for companies, tax is a burden that can reduce the company's income or profit. This study aims to analyze tax planning using the net method and tax planning using the gross up method. PT Aqiilah Duta Balisfa uses the net method as a measuring tool in paying income tax article 21. The results of the analysis show that tax planning for income tax article 21 using the gross up method is the most appropriate for companies to make corporate income tax efficient.